2012
DOI: 10.1159/000335084
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Patients with Small Cell Lung Carcinoma in Taiwan

Abstract: Background: Small cell lung cancer (SCLC) is the most aggressive form of lung cancer. The prognosis for SCLC patients remains unsatisfactory despite advances in chemotherapy. In this study, we sought to clarify the prognosis and treatment patterns of patients with SCLC. Methods: A cohort comprising all patients diagnosed with SCLC between January 2004 and December 2006 was assembled from the Taiwan Cancer Database. Patients were followed up until December 31, 2009, to determine overall survival. Patient surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 45 publications
2
21
1
Order By: Relevance
“…Situ and colleagues reported that the presence of metastases in multiple regional lymph nodes was associated with a worse prognosis . These data support the hypothesis that the success of limited‐stage SCCE therapy depends on the stage and type of tumor, which is similar to findings in small cell lung cancer (SCLC) …”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Situ and colleagues reported that the presence of metastases in multiple regional lymph nodes was associated with a worse prognosis . These data support the hypothesis that the success of limited‐stage SCCE therapy depends on the stage and type of tumor, which is similar to findings in small cell lung cancer (SCLC) …”
Section: Discussionsupporting
confidence: 53%
“…Kuo and colleagues reported that two of eight patients with limited‐stage SCCE received chemotherapy as their sole treatment. Partial responses were induced in these two patients; however, disseminated disease appeared rapidly, and they only survived for 15 and 20 months, respectively . Medgyesy and colleagues found that the long‐term survival of patients was lower after chemoradiotherapy because of fewer pathological complete responses in combined‐type SCCE .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The majority of patients with SCLC are extensive-stage at the time of initial diagnosis, where the cancer has spread either to the other side of the chest or to more distant locations in the body. The median survival rates are 10.3 months and 5.6 months for patients with limited- and extensive-stage disease, respectively (7). …”
Section: Introductionmentioning
confidence: 99%